Faktor Internal Yang Mempengaruhi Nilai Perusahaan: Studi Empiris Pada Sektor Perbankan Di Indonesia - Ni Nyoman Ayu Suryandari; Frischa Faradilla Arwinda Mongan (Journal of Innovative and Creativity, 2025)
This study investigates the effect of ownership structure, capital structure, dividend policy, and profitability on firm value in banking companies listed on the IDX from 2021–2023. Using purposive sampling, 11 firms with 33 observations were analyzed through multiple linear regression. The results show that managerial ownership and profitability positively affect firm value, while capital structure has a negative effect. Meanwhile, institutional ownership and dividend policy do not significantly influence firm value.